2019
DOI: 10.2147/prbm.s204389
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparing the extent and pattern of use of social networking sites by medical and non medical university students: a multi-center study</p>

Abstract: Objectives Although use of social networking sites (SNSs) for fun and leisure is escalating, educational use of SNSs by students is low. Furthermore, there is a scarcity of data about the use of SNSs by students from different faculties. This study compared patterns and extent of use of SNSs among medical and nonmedical university students. Methods A 21-statement questionnaire was administered to the students of medical colleges of two Saudi universities and nonmedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Their work found that it not only improved exam scores, but also reflective practice and empathy, both of which are essential skills for doctors. They also noted that these platforms improved learner engagement, feedback and personal development, thus reinforcing the positive effects described in the article by Guraya et al1…”
Section: Dear Editorsupporting
confidence: 68%
See 3 more Smart Citations
“…Their work found that it not only improved exam scores, but also reflective practice and empathy, both of which are essential skills for doctors. They also noted that these platforms improved learner engagement, feedback and personal development, thus reinforcing the positive effects described in the article by Guraya et al1…”
Section: Dear Editorsupporting
confidence: 68%
“…We read the article by Guraya et al1 with great interest. We were fascinated by the idea that social media could be integrated into medical curricula and be used as an educational platform in the future.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…The concern raised by the author of letter to the editor about sensitive issues of privacy and confidentiality need attention. As detailed in my article, injudicious use of SNSs by university students is never recommended as such usage will end up with breach in confidentiality and violation of societal norms and cultural boundaries 3. As we know that the students are increasingly involved in e-learning platforms that are developed and powered by institutional support.…”
Section: Dear Editormentioning
confidence: 99%